2022
DOI: 10.1016/j.cities.2021.103440
|View full text |Cite
|
Sign up to set email alerts
|

What matters for regional economic resilience amid COVID-19? Evidence from cities in Northeast China

Abstract: This paper examines how the economies of old industrial cities in Northeast China respond to the on-going COVID-19 pandemic crisis. The notion of resistance in regional economic resilience is used to explore what impact factors shape the response to the early stage of the crisis. The analysis reveals significant differences in terms of regional economic impact between COVID-19 and the 2008 financial crisis. We find that large cities are more vulnerable and exposed to the pandemic at its early stage, state agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 57 publications
6
69
1
3
Order By: Relevance
“…In the new normal period, individual strategy should be implemented, such as the “one city, one case” and “one city, one policy” strategies in China, and the urban governance capacity will play a critical role in the battle against the COVID-19 pandemic ( 53 ). This is required not only for scientific prevention and control but also for regional economic resistance and recovery ( 54 ). According to the report of the WHO-China Joint Mission on COVID-19 ( 55 ), strict isolation and social distancing measures can effectively reduce the local transmission risk after the epidemic has been imported.…”
Section: Discussionmentioning
confidence: 99%
“…In the new normal period, individual strategy should be implemented, such as the “one city, one case” and “one city, one policy” strategies in China, and the urban governance capacity will play a critical role in the battle against the COVID-19 pandemic ( 53 ). This is required not only for scientific prevention and control but also for regional economic resistance and recovery ( 54 ). According to the report of the WHO-China Joint Mission on COVID-19 ( 55 ), strict isolation and social distancing measures can effectively reduce the local transmission risk after the epidemic has been imported.…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al ( 2020 ) looked at economic resistance in regional economies in China during the COVID-19 recession and found that asymmetric resistance to the recessionary shock was due to a complex combination of infection rate, pre-pandemic regional economic health, and industrial structure, while long-term economic resilience is affected by the level of government support measures/policies. Building on this, Hu et al ( 2021 ) found that the higher resistant regional economies in Northeast China were positively impacted by lower infection rates, lower economic openness, and industrial specialization. Industrial specialization as a positive impact on resistance may appear contradictory, but the Northeast China regional economies specialize in industries that tend to be government-controlled and thus insulated from global supply chains issues (Hu et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Building on this, Hu et al ( 2021 ) found that the higher resistant regional economies in Northeast China were positively impacted by lower infection rates, lower economic openness, and industrial specialization. Industrial specialization as a positive impact on resistance may appear contradictory, but the Northeast China regional economies specialize in industries that tend to be government-controlled and thus insulated from global supply chains issues (Hu et al 2021 ). While government policy is treated as an input on economic resistance, the current literature lacks a comprehensive study on how government policy can directly influence which industrial structures generate positive or negative impacts on economic resistance to the COVID-19 recession.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Research on the concept of economic resilience has been published previously, as researched by Wang et al (2021), which states that the ability to withstand various pressures and risks to economic resilience can strengthen the ability of the economy to resist all external disturbances and restore its development. In addition, exploration of various factors that have an impact in responding to the initial crisis needs to be applied to regional economic resilience, especially in big cities that are more vulnerable and exposed to pandemics (Hu et al, 2021), dynamic economic resilience has a focus on the recovery process and continuous improvement of economic output to improve post-disaster economic recovery more effectively (Zhang et al, 2021), geographical economic resilience has an unstable general condition so that it has a dependence on local attributes including economic structure, human actions, and institutional arrangements (Mai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%